(untitled) (Journal of the College of Basic Education, 2022)
The increased interest in sports psychology recently in a large way on various levels of sports has great importance and its impact on the level of the player and his accomplishments because he works on studying all positive and negative psychological aspects and works on developing positive ones and avoiding the negative so that the player can reach the best achievements . As for the most important assumptions, there are statistically significant conditions between the results of tribal and posttest tests in both psychological fitness and skillful performance in soccer for the halls, and the presence of statistically significant conditions between the results of the dimensional tests of the experimental and control groups and in favor of the experimental group. As for the human field, they are players of the first Rusafa football team in the galleries. The number of (20) players by (10) players in each group, and the most important conclusions were that the exercises (psychological and skill) had a positive impact on both psychological fitness and skill performance in football halls, but the most important recommendations were to conduct studies similar to the current study on the rest of the games. Psychological fitness. Psychological exercises. And skillful performance.